Bridging the knowledge gap: Impact of nutrition and moringa-based intervention on health cadres in Manjung Village, Wonogiri - Husain, Fida'; Ambarwati, Ambarwati; Wahyuni, Wahyuni; Khasanah, Aulia Uswatun; Muslimah, Etika; Sofyan, Aan (Universitas Muhammadiyah Magelang, 2025)
The persistent issue of malnutrition in Manjung Village, Wonogiri Regency, is significantly exacerbated by limited economic access and a lack of diversity in the available nutritious food sources within the community. This community service program aimed to enhance the knowledge of Posyandu health cadres regarding the importance of balanced nutrition for children. The initiative focused on three main areas: education on essential nutritious food materials, innovative food processing, and the effective utilization of local resources, specifically Moringa leaves, as a health supplement. The activity, conducted on October 19, 2024, involved 23 Mawar Posyandu cadres and employed a lecture method combined with interactive discussions to maximize active participation. Evaluation results demonstrated a significant increase in understanding: knowledge of malnutrition improved from 21.7% to 86.9% in the high category, while comprehension of Moringa leaf utilization increased from 17.4% to 91.3% in the same category. This educational initiative proved highly effective in substantially increasing the technical knowledge of health cadres, thereby contributing directly to efforts to mitigate malnutrition in the community. Furthermore, the program encourages the sustainable utilization of local resources, such as Moringa leaves, as a long-term approach to improving public health.